Effect of gestational age and intrauterine nutrition on plasma transferrin and iron in the newborn. Issue 10 (October 1975) - Scott, P H; Berger, H M; Kenward, C; Scott, P; Wharton, B A
Abstract : Plasma concentrations of transferrin and iron were measured in the cord blood of babies of varying gestational age and birthweight. Tranferrin and iron concentrations rose with gestational age; values in light-for-dates babies did not differ from those in babies of appropriate weight. In the last trimester of pregnancy plasma transferrin and iron concentrations in the fetus are affected by the maturity of the pregnancy but are independent of the nutritional status of the fetus. The low transferrin levels, particularly in preterm babies, may caution the use of iron especially by the parenteral route in the neonatal period, but we are wary of abandoning on this evidence alone the well tried clinical custom of giving oral iron to preterm babies who are not breast fed.